OP035 NUDT15 variants contribute to thiopurine-induced myelosuppression in European populations. (16th January 2018) - Walker, G; Harrison, J; Voskuil, M; Heap, G; Heerasing, N; Hendy, P; Koskela, J; Daly, M; Sokol, H; McGovern, D; Weersma, R; Bewshea, C; et al.
Abstract: Background: The thiopurines (mercaptopurine [MP] and its prodrug azathioprine [AZA]) are the most commonly prescribed immunosuppressants used in the treatment of inflammatory bowel disease (IBD). However, their use is often curtailed by bone marrow suppression, which may lead to opportunistic infections and even death. 1, 2 Pre-treatment pharmacogenetic testing for TPMT variants, an enzyme known to influence thiopurine metabolism is commonly practiced, but only identifies 25% of European patients who suffer this adverse drug reaction. 3, 4 In East Asians, NUDT15 variants have also been associated with TIM. 5, 6 We aimed to identify novel genetic variants which predict TIM in European IBD patients. Methods: Design : A case–control study with rigorous assessment of causality in all cases prior to generation of whole exome sequence and genotype array data. Replication of findings was conducted in an independent cohort of cases and controls. Setting : A multicentre study recruiting participants from 82 UK and 7 international sites. Participants : 491 cases with TIM (total white cells ≤2.5 × 10 9 /l and/or neutrophils ≤1.0 × 10 9 /l) and 734 thiopurine-tolerant IBD controls identified retrospectively. Main outcome(s) and measure(s ): Association of genetic variants in cases and controls. Results: A total of 329 cases and 635 controls were used in the final analysis. We confirmed an association of TPMT with TIM, and discovered a novel 6 bp in-frame deletion (rs746071566; chromosome 13) in NUDT15 using exome sequencing (19/329 [5.8%] cases, 1/635 [0.2%] controls; odds ratio (OR) 38.2; p = 1.3 × 10 −8 ). We replicated this in an independent cohort (2/73 [2.7%] cases vs. 2/840 [0.2%] controls; OR 11.8, p = 0.034). Carriage of any NUDT15 coding variant conferred a 22-fold increase in the odds of TIM ( p = 2.8 × 10 −8 ), independent of TPMT genotype and thiopurine dose. Conclusions: Patients with defective NUDT15 alleles have excessive 6-thioguanine nucleotides (6TGN) levels and increased risk of myelotoxicity.[6] We estimate the absolute risk of TIM in NUDT15 heterozygotes is 59%. For every 100 patients genotyped, 2 patients will carry an NUDT15 mutation and need to receive an alternative treatment to prevent TIM in one patient. Pre-treatment NUDT15 genotyping should reduce TIM cases by 13%, and in addition to TPMT offer a safer personalised approach to thiopurine prescribing. References: 1. Gisbert JP, Gomollon F. Thiopurine-induced myelotoxicity in patients with inflammatory bowel disease: a review. Am J. Gastroenterol, 2008. 2. Chaparro M, Ordás I, Cabré E, et al . Safety of thiopurine therapy in inflammatory bowel disease: long-term follow-up study of 3931 patients. Inflamm Bowel Diseases. 2013. 3. Teml A, Schaeffeler E, Herrlinger KR, Klotz U, Schwab M. Thiopurine treatment in inflammatory bowel disease. Clinical Pharmacokinetics, 2007. 4. Colombel JF, Ferrari N, Debuysere H, et al ., Genotypic analysis of thiopurine S-methyltransferase in patients with Crohn's disease and severe myelosuppression during azathioprine therapy. Gastroenterology, 2000. 5. Yang S-K, Hong M, Baek J, et al. A common missense variant in NUDT15 confers susceptibility to thiopurine-induced leukopoenia. Nat. Genetics, 2014. 6. Moriyama T, Nishii R, Perez-Andreu V, et al . NUDT15 polymorphisms alter thiopurine metabolism and haematopoietic toxicity. Nat Genetics, 2016.